ION-INDUCED DNA GRAPHENE FIELD EFFECT TRANSISTOR CURRENT MODULATION - MOHD NORHAKIM, NURUL NADIA HAFIZA (2018)
Lead contamination a severe environmental problems as it is risky for human health and the environment. Lead are toxic and harmful as they can penetrate the human body easily through water, food, and air. Lead can cause serious health complication even though under a low dose exposure. Therefore, numerous attempt have been made to evolve sensors for detecting and monitoring lead ion as an initiative for treating lead contamination. As such, various methods for lead ions removal from water have been introduced but due to their limitations, a more effective method is highly required. Hence, a DNA Graphene Field Effect Transistor (GFET) has been developed in this study as another alternative for lead ion detection. In this work, the sensor is fabricated and characterized to analyzed its sensitivity and selectivity for the detection of lead in contaminated water sources. The graphene attached on the sensor is synthesized using a Low-Pressure Chemical Vapor Deposition (LPCVD) and is functionalized with the Guanine-rich DNA to enhance the sensing element of the sensor. This project involves two main phases which are sensor fabrication and the characterizations of the sensor. Then the sensitivity of the sensor towards the lead ions are observed using Agilent B1500a Semiconductor Parameter Analyzer where the I-V characteristics of the sensor are analyzed to determine its sensitivity towards lead ions. The fabricated sensor shows typical GFET I-V characteristics with a minimum point known as the charge neutrality point (CNP) where the shift of CNP is used as the sensor’s response. With high sensitivity towards the lead ions, the sensor designed which can sense the availability of lead ions under the concentration as low as 20nM can be further developed into a portable instrument as a sensing device for lead detection.